Implementasi Kepribadian Islami Mahasiswa Ilmu Kesehatan Dalam Pembelajaran Kewarganegaraan - Bambang Wahrudin; Desy Oktaviany; Rania Nurhayati; Alentio Qa’albinovel (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2023)
The concept of Islamic personality encompasses the traits and values that define members of the Muhammadiyah Student Organization in their daily conduct. It also serves as the foundational principle and guiding framework for Muhammadiyah’s charitable missions and struggles. The integration of Islamic personality within the citizenship education process plays a vital role in shaping strong moral character and civic consciousness among the younger generation. This study aims to examine how students’ Islamic personalities are implemented during citizenship learning. The research was conducted with students from the Faculty of Health Sciences at Muhammadiyah University of Ponorogo, employing a quantitative descriptive method. Data were collected through questionnaires distributed to respondents. The findings reveal that students possess a good understanding of Muhammadiyah’s personality values and successfully apply them both in the citizenship learning process and in their everyday lives. Moreover, these Muhammadiyah personality values provide a platform for students to embody and practice Muhammadiyah principles not only within academic contexts but also through tangible participation in social and national life.